PENGARUH PENGETAHUAN AKUNTANSI, PENGETAHUAN E-FILING, DAN SOSIALISASI PAJAK TERHADAP LEPATUHAN PAJAK UMKM - Ridha, Nadya Salma; Ulupui, I Gusti Ketut Agung; Zairin, Gentiga Muhammad (LPPM Universitas Bina Bangsa, 2024)
This research was conducted with the aim of examining the effect of accounting implementation, e-filing implementation and tax outreach on MSME tax compliance. This research uses primary data with a sample of MSMEs in the Serpong District Area, South Tangerang. This research used a survey system (questionnaire) with 102 MSME respondents. Hypothesis testing uses multiple linear regression analysis methods and using SPSS 26. Taxpayer compliance is an act of being obedient and aware of the orderly payment and reporting of tax obligations. Taxpayers can be said to be compliant if a person or an entity/company is aware of their discipline in depositing and reporting their tax obligations both periodically and annually in accordance with applicable laws